2012
DOI: 10.1177/1075547011434991
|View full text |Cite
|
Sign up to set email alerts
|

“Dr. Soundbite”

Abstract: Bioethicists have been increasingly used as expert sources in science and medical stories involving ethical issues. This case study examines how and why one bioethicist, Dr. Arthur L. Caplan, has become so ubiquitous. Organizational news routines provide the theoretical framework for a newspaper content analysis and interviews. As part of journalists’ small roster of trusted experts, Caplan has been the de facto bioethics representative for two decades, helping shape media discourse on bioethical issues. Capla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 33 publications
(58 reference statements)
0
4
0
3
Order By: Relevance
“…A study of the use of one bioethicist as a US media source suggested he was called on so often because he "understands news routines, provides pithy quotes, and supports public engagement". (Kruvand, 2012) This tallied with Howell's 'Expert Women' survey results, where some experts (predominantly but not exclusively male) were called on repeatedly by broadcasters.…”
Section: Hearing the Disparitiesmentioning
confidence: 92%
“…A study of the use of one bioethicist as a US media source suggested he was called on so often because he "understands news routines, provides pithy quotes, and supports public engagement". (Kruvand, 2012) This tallied with Howell's 'Expert Women' survey results, where some experts (predominantly but not exclusively male) were called on repeatedly by broadcasters.…”
Section: Hearing the Disparitiesmentioning
confidence: 92%
“…Studies show, for example, that the status within the science system influences journalistic selection, but at least occasionally also the local or regional proximity as well as the accessibility and communication ability of a source and its willingness to provide information quickly and up-to-date. Additionally, what an expert says is of importance, especially in controversy (e.g., Boykoff & Boykoff, 2004;Conrad, 2016;Kruvand, 2009;Kruvand, 2012;Nölleke, 2009;Peters, 1994;Peters, 2014;Rothman, 1990; Schütz-Ierace, 2010).…”
Section: The Selection Problem -Defining Expertise and Identifying Scmentioning
confidence: 99%
“…Estudios anteriores confirman que la elocuencia, la accesibilidad y el conocimiento son los factores que, junto a la flexibilidad para seguir las rutinas de producción, inciden a la hora de seleccionar fuentes expertas (Kruvand, 2012). También el que ya hayan estado expuestos en los medios repercute positivamente en la selección (Van Dijk, 2004;Boyce, 2006).…”
Section: Sobre Las Fuentes Expertasunclassified
“…Como sucede en otros medios, los productores y productoras audiovisuales siguen rutinas de trabajo que no solo determinan cómo llevan adelante la tarea, sino que también reflejan el encuadre de la información (Tuchman, 1978(Tuchman, y 1979Shoemaker & Reese, 1996;García Marín, 2007). Comprender estas rutinas y cómo impactan en la selección de fuentes expertas es un primer paso para abordar un tema que no ha sido aun suficientemente estudiado (Boyce, 2006;Sumpter y Garner, 2007;Kruvand, 2012).…”
Section: Introductionunclassified